2019
DOI: 10.1038/s41416-019-0458-x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of inflammatory markers for cancer diagnosis in primary care: a prospective cohort study using electronic health records

Abstract: BackgroundEarly identification of cancer in primary care is important and challenging. This study examined the diagnostic utility of inflammatory markers (C-reactive protein, erythrocyte sedimentation rate and plasma viscosity) for cancer diagnosis in primary care.MethodsCohort study of 160,000 patients with inflammatory marker testing in 2014, plus 40,000 untested matched controls, using Clinical Practice Research Datalink (CPRD), with Cancer Registry linkage. Primary outcome was one-year cancer incidence.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 30 publications
4
56
0
Order By: Relevance
“…There was a significant difference between studied groups regarding platelets, lowest platelet number was detected in cancer group, there was nonsignificant difference between studied groups regarding WBCs, and highest WBCs number was detected in cancer group (8.05±2.3) as shown in table (2) this is in agreement with Morikawa et al [2] who concluded that the FIT relies on the antibodies that bind to the globin, the decomposition of the Hb influences the tool's detection ability, and it is possible that bleeding from proximal colon may lead to an underestimation of the Hb level. Also this agrees with Jessica Watson et al [3] who declared that Cancer risk is greater with higher inflammatory marker levels, with older age and in men; risk rises further when a repeat test is abnormal but falls if it normalizes. Men over 50 and women over 60 with raised inflammatory markers have a cancer risk which exceeds the 3% NICE threshold for urgent investigation.…”
Section: Discussionsupporting
confidence: 90%
“…There was a significant difference between studied groups regarding platelets, lowest platelet number was detected in cancer group, there was nonsignificant difference between studied groups regarding WBCs, and highest WBCs number was detected in cancer group (8.05±2.3) as shown in table (2) this is in agreement with Morikawa et al [2] who concluded that the FIT relies on the antibodies that bind to the globin, the decomposition of the Hb influences the tool's detection ability, and it is possible that bleeding from proximal colon may lead to an underestimation of the Hb level. Also this agrees with Jessica Watson et al [3] who declared that Cancer risk is greater with higher inflammatory marker levels, with older age and in men; risk rises further when a repeat test is abnormal but falls if it normalizes. Men over 50 and women over 60 with raised inflammatory markers have a cancer risk which exceeds the 3% NICE threshold for urgent investigation.…”
Section: Discussionsupporting
confidence: 90%
“…Nicholson et al 6 describe the risk of cancer diagnosis following recorded weight loss in primary care consultations; they estimate this risk to be 1.2% by the end of a 3-month follow-up period, increasing to 1.8% by 12 months. Watson et al 7 examined the risk of cancer following tests for inflammatory markers (such as erythrocyte sedimentation rate, Creactive protein and plasma viscosity) in primary care; they estimate the risk to be 3.5% in patients with raised values by 12 months. Together with other studies estimating the predictive value of different symptoms and pre-diagnostic features, these estimates can support decision making at the clinical encounter and the production of clinical practice guidelines.…”
Section: Mainmentioning
confidence: 99%
“…Further, the authors of both commented studies appropriately compared the characteristics of patients with and without recorded weight or recorded inflammatory marker tests, as such analyses can help to assess the generalisability of their findings. 6,7 Unlike information about the presence/absence of symptoms, information about the results of diagnostic tests could additionally allow for appreciation of 'dose-response' associations (e.g. using exact inflammatory marker, 7 or platelet count, 13 values), which could enable further individualising of risk estimates.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no signs or symptoms that are specific for an elevated C-reactive protein level, because it is not a specific test. Signs or symptoms, if present, would depend on the underlying inflammatory condition that is the cause of the elevated CRP level (19). CRP is an inflammatory marker which is typically not detected in the blood unless some degree of inflammation is present in the body (20).…”
Section: E J M Rmentioning
confidence: 99%